Problems of Translating English Idiomatic Expressions into Arabic - Lubna M. Khoshaba (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Idioms have been defined as groups of words or phrases used together to have fixed meanings. No doubt, ideas or thoughts have been expressed differently in different languages. Using the idiomatic expressions is one of the ways that can be used to convey the intended meaning indirectly. Many researches have been carried out in this respect to show the importance of idioms and how problematic it is the process of translating them from one language into another knowing that this phenomenon is culture-specific. This research paper aims at translating idiomatic expressions from English into Arabic. The current study ends with the following conclusions: (1) idioms are culture specific, (2) Idioms are of two kinds. They are a: transparent and b: opaque, and (3) most idiomatic expressions were translated communicatively and in certain cases adaptation was used. These two types of translations result in effective renderings.